Profile of Meningioma based on Imaging and Histopathology at Dr. Saiful Anwar Hospital, Malang - Agung Setiawan; Krisna Ayu (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2026)
Introduction: Meningiomas are common central nervous system tumors originating from meningothelial cells. Imaging examinations are widely used to characterize lesion features, while histopathological evaluation remains essential for definitive diagnosis and grading. Material and Methods: This study was a retrospective descriptive study conducted using secondary data from medical records of patients diagnosed with meningioma at RSUD Dr. Saiful Anwar Malang between 2020 and 2023. Data included demographic characteristics, imaging findings from CT and MRI examinations, and histopathological grading. Results: Most meningioma cases occurred in female patients (85%), with the highest proportion observed in the 40–60-year age group (65%). According to the WHO classification, grade I meningiomas were the most common (69%). The frontal region was the most common tumor location (25%), followed by involvement of multiple regions (35%). Solitary meningiomas accounted for 87% of cases. Most tumors had a maximum diameter of 4–6 cm (67%). Imaging findings commonly included dural tail (51%), hyperostosis (53%), and peritumoral vasogenic edema, which was qualitatively identified in all cases. Conclusion: This retrospective descriptive study demonstrates the demographic distribution, imaging characteristics, and histopathological grading of meningioma cases at a tertiary referral center. Imaging features such as dural tail, hyperostosis, and peritumoral edema were frequently observed; however, histopathological examination remains the gold standard for definitive diagnosis and grading of meningioma.